Governance and management in higher education - Sengupta, Enakshi; Blessinger, Patrick; Nezaami, Nasiruddin (Innovations in higher education teaching and learning, 2022)
Autonomy in governance and management in education has become the prerogative of higher education institutions, whilst optimum allocation and use of resources have become the aim of all higher education institutions. This book volume explores the creation of knowledge and its dissemination in an appropriate manner so as to create a significant impact in society. The chapter authors talk about the highly competitive education market and the transformation it has undergone. Authors from across the globe have suggested interventions that will help in sustainable growth of universities while maintaining and enhancing their quality standards. The chapters present a better understanding of a philosophy of management, society, development and education.